2015
DOI: 10.3109/09638288.2015.1061603
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of everyday activities post-stroke

Abstract: Stroke survivors' lived experiences of pleasure, productivity and restoration in the context of everyday activities yields insight into the survivors' recovery and adjustment processes and into their quality of life. Practitioners should therefore incorporate stroke survivors' experiences as they facilitate goal setting and plan interventions. Implications for Rehabilitation Understanding stroke survivors' lived experiences provides practitioners valuable information to assist with goal setting and interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Although most studies have collected data on patient stroke experiences weeks or even years after their stroke (Sarre et al., ), much less is known about their initial experiences after discharged directly home from the hospital. Atler () found that understanding daily activities of stroke survivors can provide insight into their recovery and care needed. Stroke survivors who are discharged home also have continued issues 6–8 months after discharge (Taule & Råheim, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies have collected data on patient stroke experiences weeks or even years after their stroke (Sarre et al., ), much less is known about their initial experiences after discharged directly home from the hospital. Atler () found that understanding daily activities of stroke survivors can provide insight into their recovery and care needed. Stroke survivors who are discharged home also have continued issues 6–8 months after discharge (Taule & Råheim, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sedentary behavior is evident and has adverse effects for individuals with stroke (Alzahrani et al., 2011; Atler, 2016). More recently, the duration of time spent on sedentary behavior has been associated with cardiovascular disease risk, type 2 diabetes, breast and colon cancers, and cardiovascular and all-cause mortality (Tremblay et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the RATULS trial participants' accounts of stroke were strongly aligned with the existing qualitative literature concerning the multifaceted impacts of stroke, 68,69,77 variable nature of recovery over time 76,78,79 and expression of hopes and expectations concerning fuller recovery over time. 76,80 Participating in the RATULS trial was viewed by patients as an opportunity to extend or supplement their recovery process, particularly in relation to upper limb rehabilitation. Some participants expressed disappointment on being allocated to the usual care group.…”
Section: Qualitative Process Evaluationmentioning
confidence: 99%